The importance of assistive technology in the productivity pursuits of young adults with disabilities. - Ripat, Jacquie D.; Woodgate, Roberta L. (Work, 2017)
BACKGROUND: Young adults with disabilities often use assistive technology (AT) to address personal needs, engage in communities and pursue educational and vocational goals. Little is known about their personal experiences and challenges of accessing and using AT for productivity-related activities. OBJECTIVE: This study aimed to learn from young adults about their experiences and use of AT in supporting their productivity. METHODS: Using a qualitative approach, 20 young adult AT users engaged in semi-structured interviews and a photovoice process. Data were analysed inductively. RESULTS: Three primary themes were identified: I Have to Figure it out Myself, With the Right AT, and Relational Aspects of AT Use. Although participants were experienced AT users, they were often left alone to figure out their emerging needs. They relied on AT to participate in productivity pursuits however stigma around AT use in unsupportive work environments were new concerns. CONCLUSIONS: Young adults with disabilities draw on their experiences of AT use but may need to develop advocacy skills to ensure their needs are met in productivity-related environments. Employers and supervisors should recognize AT as essential to young adult's engagement with productivity-related activities and have an important role in developing inclusive work environments.